A New Hope: Self-Assembling Peptides with Antimicrobial Activity - Lucia Lombardi; Annarita Falanga; Valentina Del Genio; Stefania Galdiero (MDPI AG, 2019)
Peptide drugs hold great promise for the treatment of infectious diseases thanks to their novel mechanisms of action, low toxicity, high specificity, and ease of synthesis and modification. Naturally developing self-assembly in nature has inspired remarkable interest in self-assembly of peptides to functional nanomaterials. As a matter of fact, their structural, mechanical, and functional advantages, plus their high bio-compatibility and bio-degradability make them excellent candidates for facilitating biomedical applications. This review focuses on the self-assembly of peptides for the fabrication of antibacterial nanomaterials holding great interest for substituting antibiotics, with emphasis on strategies to achieve nano-architectures of self-assembly. The antibacterial activities achieved by these nanomaterials are also described.